Posterior ankle impingement syndrome clinical features are not associated with imaging findings in elite ballet dancers and athletes - Baillie, P.; Ferrar, K.; Cook, J.; Smith, P.; Lam, J.; Mayes, S. (Clinical Journal of Sport Medicine, 2022)
Objective: To assess the association between clinical features and magnetic resonance imaging (MRI) findings in posterior ankle impingement syndrome (PAIS) and to compare the prevalence of imaging findings between participants with and without a clinical diagnosis of PAIS. Design: Case-control study. Setting: Elite ballet and sport. Participants: Eighty-two male (54%) and female participants comprising ballet dancers (n = 43), cricket fast bowlers (n = 24), and football (soccer) players (n = 15). Independent Variables: Clinical: posterior ankle pain on body chart, passive plantarflexion pain provocation test. Patient-reported outcome measures: Oslo Sports Trauma Research Center Overuse Injury Questionnaire, Foot and Ankle Ability Measure Sports subscale. Main Outcome Measures: Imaging findings including posterior ankle bone marrow edema, os trigonum (± bone marrow edema, and increased signal at synchondrosis), Stieda process (± bone marrow edema), talocrural and subtalar joint effusion-synovitis size, flexor hallucis longus tendinopathy, and tenosynovitis identified as present or absent on 3.0-Tesla MRI. Results: Imaging findings were not associated with posterior ankle pain or a positive ankle plantarflexion pain provocation test. Imaging findings were not associated with patient-reported outcome measures. Imaging findings did not differ between PAIS-positive and PAIS-negative groups. Os trigonum and Stieda process were prevalent despite clinical status. Conclusions: The lack of association between imaging findings and clinical features questions the role of imaging in PAIS. Clinicians should rely primarily on clinical assessment in the diagnosis and management of patients with PAIS.